2008
DOI: 10.1210/jc.2007-2759
|View full text |Cite
|
Sign up to set email alerts
|

Serum Levels of Retinol-Binding Protein 4 and Adiponectin in Women with Polycystic Ovary Syndrome: Associations with Visceral Fat But No Evidence for Fat Mass-Independent Effects on Pathogenesis in This Condition

Abstract: Although associated with visceral fat, serum RBP4 and adiponectin levels do not play important, fat-mass-independent primary roles in the development of PCOS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 40 publications
3
34
1
Order By: Relevance
“…Albumin was measured by Laurell rocket immunoelectrophoresis, using polyclonal antiserum from International Immunology (Murrieta, CA). Adiponectin (total and high molecular mass) was assayed by an "in house" ELISA, using monoclonal antibodies as described previously (2). Low-molecular mass adiponectin concentrations were calculated by subtraction of high molecular mass from total concentrations.…”
Section: Methodsmentioning
confidence: 99%
“…Albumin was measured by Laurell rocket immunoelectrophoresis, using polyclonal antiserum from International Immunology (Murrieta, CA). Adiponectin (total and high molecular mass) was assayed by an "in house" ELISA, using monoclonal antibodies as described previously (2). Low-molecular mass adiponectin concentrations were calculated by subtraction of high molecular mass from total concentrations.…”
Section: Methodsmentioning
confidence: 99%
“…Although this topic has been investigated by many research groups, there is still no clear evidence of a direct relationship between hypoadiponectinemia and PCOS. A number of studies showed an independent decrease in adiponectin levels in PCOS patients [108,[112][113][114][115][116][117][118], but others failed to demonstrate a direct link between hypoadiponectinemia and PCOS [119][120][121][122][123][124][125][126][127][128][129]. Whether hypoadiponectinemia is or is not directly implicated in the development of PCOS, it surely participates in the insulin-resistant state observed in those patients, and there has been speculation that hypoadiponectinemia could be used to identify women with PCOS who are at higher risk for the future development of type 2 diabetes [130] and coronary artery diseases (CAD) [117].…”
Section: Polycystic Ovary Syndromementioning
confidence: 99%
“…One possible postulated mechanism is up-regulation of mRNA RBP4 by 17β-estradiol, a hormone derived from testosterone that is mainly responsible for PCOSassociated clinical hyperandrogenism [7]. However, in contrast to these results, a few previous studies [8,26,27] have stated that there are no differences in RBP4 levels between PCOS cases and controls and have suggested a primary role of RBP4 in the development of PCOS. It is possible that this process involves other molecular mechanisms that remain to be elucidated.…”
Section: Discussionmentioning
confidence: 92%
“…In overweight women with PCOS compared with controls, enhanced expression of RBP4 in adipose tissue and elevated serum RBP4 have been described [7]. In a study involving 50 women with PCOS and 28 control women, the result showed indistinguishable levels of RBP4 between the two groups [8]. In a subsequent study on 27 lean women with PCOS and 19 age-and body mass index-matched controls, RBP4 levels were also shown to be similar between the two groups [9].…”
Section: Description Of the Studiesmentioning
confidence: 98%